Decentralized Point-of-Care Manufacturing of CD19 Chimeric Antigen Receptor T Cells in Mexico - Rosario Salazar-Riojas; Dalila M. Alvarado-Navarro; Yair O. Chávez-Estrada; Ana K. Hernández-Navarro; Martha B. Ake-Uc; Nidia K. Moncada-Saucedo; José C. Jaime-Pérez; Sofía I. Quezada-Ramírez; Anna C. Rodriguez-Zuñiga; David Gómez-Almaguer; Andrés Gómez-De León (JCO Global Oncology)
PURPOSETo validate and replicate an automated decentralized CD19 chimeric antigen receptor T (CAR-T) cell manufacturing process from healthy adult volunteers in an academic institution in a middle-income country.METHODSHealthy volunteers were recruited and underwent leukapheresis with the continuous mononuclear cell (MNC) collection protocol. Clinical-grade CAR-T cell manufacturing was performed in a closed system using a second-generation CD19 vector with 41BB costimulatory domain. Quality control was assessed at different points in the production process with prespecified release criteria including product's aspect, sterility, cell viability, impurity, and quantity. The target dose formulation was 1 × 106/kg viable CAR-T cells per volunteer.RESULTSFive healthy volunteers were recruited, all donated adequate MNC units, and successfully underwent the manufacturing process. After T-cell culture harvest, the products contained a median CAR-T cell concentration of 16.5 × 106/mL (range, 7.7-22.2 × 106/mL), with a median transduction percentage of 44.7% (range, 39.2%-60.5%) and a median CD3+ cell viability of 97.7% (range, 90.4%-98.7%). Sterility was maintained throughout the manufacturing process. The quantity of cells harvested per kilogram of body weight was 24.6 MB-CART19.1 cells × 106/kg (range, 9.3-33.1 × 106/mL). The quality was similar in both fresh and cryopreserved units. Dose formulations were 1.1 CAR-T cells × 106/kg (range, 1.0-1.2 CAR-T cells × 106/kg).CONCLUSIONOur study demonstrates an effective methodology with satisfactory and comparable performance to international reports. Point-of-care manufacturing is a feasible alternative to increase access to CAR-T cells in academic centers.